INVENTARISASI TUMBUHAN PAKU DI DAERAH MALANG - Sunarmi; Sarwono (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2004)
Inventory is a way to collect the data of plants in a region which usually started by activity of collection, description, identification and ended with classification. The variety of Indonesia flora until today have been discovered totally . This research aimed to know the species of fern plants which grow in Malang area. Research had done in March 2001–February 2002 with descriptive method, explores technique, and documentation. Research subject were all of species of fern plants grow in Malang area. Identification to be conducted by comparing entire characteristic exist in found plant with key identify loaded by species of fern plants in Flora Malesiana and some relevant book. Result of research shows that in Malang found 50 species, 28 genus, 15 family, and 4 class from species of fern plants. Suggested to conduct research of inventory of other plants which exist in Malang area to equip flora in Indonesia